An analysis of speech act in whatsapp - Syawal, La Ode Muhamad Irwin; Mardin, Muhammad Ikhwan; Saleh, Husna; Fuad, M. Noor; As’Ad, Muhammad (Indonesia Berdaya, 2024)
Language is a crucial aspect of our lives, serving as a bridge for communication among individuals. People use language to convey emotions, ideas, desires, and feelings. One platform for communication is WhatsApp. Many people enjoy chatting on WhatsApp, but not all of them grasp the meaning behind each utterance spoken or sent by the speaker or sender. Various linguistic aspects, including speech acts, can be explored on WhatsApp, such as pragmatics, semantics, and sociolinguistics. This study aims to analyze the factors that lead to misunderstandings when performing perlocutionary acts on WhatsApp and how locutionary acts influence perlocutionary acts on the platform. The research findings identify several causes of misunderstandings in the communication process through WhatsApp. Firstly, incorrect punctuation usage contributes to misunderstandings. Secondly, typographical errors are another common factor. Thirdly, incomplete sentences resulting from typing too quickly make it challenging to comprehend the intended message. Fourthly, issues such as poor network connectivity lead to only a fraction of the message reaching the recipient. Additionally, locutionary acts represent the literal meaning of a sentence. The conclusion of this research is the impact of locution on perlocution depends on how effectively locution can convey instructions or meanings of the spoken sentence. If the utterance is not well-understood by the listener, they may not execute or comprehend the intended meaning, leading to perlocutionary acts and miscommunication between the individuals involved.